Antioxidant, pro-oxidant effect of the thiosemicarbazone derivative Schiff base (4-(1-phenylmethylcyclobutane-3-yl)-2-(2-hydroxybenzylidenehydrazino) thiazole) and its metal complexes on rats - Karatepe, Mustafa; Karatas, Fikret (Wiley, 2006)
Adverse biological activities of thiosemicarbazone (TSC) and Schiff base (SB) derivatives have been widely studied in rats and in other animal species using different doses, times and routes of administration. However, there are few studies describing changes in some biochemical parameters in vivo which are indicative of oxidative stress in biological systems and of morphological changes of tissues. In this study, the rats were injected subcutaneously with a new thiosemicarbazone thiazole ring containing a Schiff base (LH) and its Cu(L)(2) and Zn(L)(2) complexes (25 mg kg(-1) body weight) and then sacrificed after 1, 2, 4, 8, 16, 32 and 64 days. The aim of this study was to determine the effect of the new compounds on the serum antioxidant vitamins (A, E, C), selenium (Se), malondialdehyde (MDA) levels, erythrocyte GSH-Px enzyme activity and morphological changes in the liver, kidney and adrenal gland tissues. It was observed that erythrocyte GSH-Px activity, serum MDA and vitamins A, E concentrations were statistically changed (p < 0.02), but serum levels of selenium, and vitamin C were not changed. In conclusion, the parameters measured show that Cu(L)(2) caused considerable oxidative stress and Zn(L)(2) behaved as an antioxidant. No oxidative stress in LH was observed compared to the control group. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: thiosemicarbazone; Schiff base; cyclobutane; antioxidant vitamins; GSH-Px; malondialdehyde; rat